SABRE enhancement with oscillating pulse sequences. Issue 27 (12th May 2022) - Li, Xiaoqing; Lindale, Jacob R.; Eriksson, Shannon L.; Warren, Warren S.
Abstract : Oscillating pulse SABRE (Signal Amplification by Reversible Exchange) that uses magnetic fields far away from the resonance condition of continuous excitation can triple the polarization. The oscillating pulse, in effect, adjusts the J-couplings between hydrides and target nuclei. Abstract : SABRE (Signal Amplification by Reversible Exchange) methods provide a simple, fast, and cost-effective method to hyperpolarize a wide variety of molecules in solution, and have been demonstrated with protons and, more recently, with heteronuclei (X-SABRE). Here, we present several oscillating pulse sequences that use magnetic fields far away from the resonance condition of continuous excitation and can commonly triple the polarization. An analysis with average Hamiltonian theory indicates that the oscillating pulse, in effect, adjusts the J-couplings between hydrides and target nuclei and that a much weaker coupling produces maximum polarization. This theoretical treatment, combined with simulations and experiment, shows substantial magnetization improvements relative to traditional X-SABRE methods. It also shows that, in contrast to most pulse sequence applications, waveforms with reduced time symmetry in the toggling frame make magnetization generation more robust to experimental imperfections.